Clinical relevance of a newly developed endometrial receptivity test for patients with recurrent implantation failure in Japan. (7th February 2022) - Ohara, Yasuhiro; Matsubayashi, Hidehiko; Suzuki, Yosuke; Takaya, Yukiko; Yamaguchi, Kohei; Doshida, Masakazu; Takeuchi, Takumi; Ishikawa, Tomomoto; Handa, Mika; Miyake, Tatsuya; Takiuchi, Tsuyoshi; Kimura, Tadashi
Abstract: Purpose: To assess the clinical efficacy of personalized embryo transfer (pET) guided by a new endometrial receptivity test, ERPeak SM, in patients with recurrent implantation failure (RIF). Methods: Recurrent implantation failure patients of all ages at two private Japanese clinics from April 2019 to June 2020 were retrospectively analyzed. The intervention group ( n = 244) received pET in accordance with endometrial receptivity testing results and was compared to control group ( n = 306) receiving standardized timing, non‐personalized embryo transfer (npET). In propensity score matching analysis, the clinical pregnancy rate (CPR) and live birth rate (LBR) were compared between groups, and a subanalysis of advanced maternal age (AMA) (≥38 years old) versus non‐AMA (<38 years old) patients was also conducted. Results: The CPR and LBR of the pET group were significantly higher than those of the npET group (37.7% vs. 20.0%, adjusted OR: 2.64; 95%CI, 1.70–4.11, p < 0.001 and 29.9% vs. 9.7%, adjusted OR: 4.13; 95%CI, 2.40–7.13, p < 0.001, respectively). Furthermore, in the subanalyses, the CPR and LBR of the pET group were significantly higher than those of the npET group in both the AMA non‐AMA patients. Conclusions: The new ERPeak SM endometrial receptivity test is a useful alternative diagnostic tool for poor‐prognosis patients, regardless of age. Abstract : Personalized embryo transfer guided by a new endometrial receptivity test significantly improved clinical pregnancy rate and live birth rate in patients with recurrent implantation failure, regardless of age.